Use of Silicon Vaginal Pessary for Treatment of Pelvic Organ Prolapse - Mazumder, Afroza Akther; Begum, Shamim Ara; Yousuf, Nadia (Journal of Chittagong Medical College Teachers’ Association, 2022)
Background: Use of vaginal pessary as a conservative therapy for pelvic organ prolapse is very common and upto 77% of clinicians uses ring pessary for 1 line management of prolapse. Aim to treat prolapse by conservative approach is to alleviate the symptoms of prolapse and avert or delay the need for surgery. Aim of this study was to find out improvements of symptoms related to pelvic organ prolapse and satisfaction rate after 3 months of using vaginal pessary. Materials and methods: A prospective observational study was conducted from January 2019 –to June 2019 in the Department of Gynaecology and Obstetrics of Bangabandu Memorial Hospital, Chattogram. Total 31 patients were included with symptomatic Pelvic Organ Prolapse (POP) willing to use pessary. Primary outcome were improvement of symptoms and their satisfaction from baseline to 3 months. Results: Age of the respondents were between 25-80 years with a mean of 50 ( +-12) years, maximum respondents were postmenopausal 54.8% .Out of 31 respondents 27(87.1%) continue pessary use upto 3 months and their after, 2(6.5%) cases spontaneous expulsion took place, 2(6.5%) discontinue the use. Compare with base line findings significant improvement in patients symptoms were observed at 3 months. Nearly all symptoms related to pelvic organ prolapse resolved from baseline to to 3 months: buldge (92.3% to 7.7% , p < 0.001), dragging pain in lower abdomen (100% to 14.8% , p<0.001). Urinary symptoms voiding difficulty improved in 88% ( p<0.001), urinary urgency improved in 81.8% (p<0.001), urge and stress incontinence improved in 100% (p<0.001). Incomplete empting of bowel improved in 100%(p<0.001). During follow up 4(12.9%) women complain of vaginal discharge. At 3months 88.9% women were satisfied with pessary and 3(11.1%) were dissatisfied. Conclusion: This study showed that treatment with use of ring pessary in women with pelvic organ prolapse had significant improvements in the symptoms with high satisfaction rate. JCMCTA 2022 ; 33 (1) : 118-123